HISTOPATHOMICROBIAL EXAMINATION OF ECHINOCOCCOSIS IN LUNG AND LIVER INFECTED WITH KLEBSIELA PNEUMONIA IN SHEEP OF IRAQ. - Hashim, M. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
Investigation about hydatid cyst infection in lungs and liver of sheep and  its association with Klebsiella pneumonia  was done ,specimens were collected from sick and healthy sheep at  different slaughter    houses in  Iraq Cities, each specimens which contained cystic lesions  were divided to three parts , 1st part was sent to microbial laboratory ,2nd part  was sent to parasitology  laboratory, 3rd part  was sent to histopathology laboratory . A number (100) of infected specimens lung and liver were examined grossly in order to look for any cystic lesions, as well as each specimen was examined microbiologically, and were positive for both Klebsiella pneumonia and parasitism. Histopathological examination grossly showed cystic lesions on surfaces of lungs and livers with paleness appearance, microscopically pathological lesion mainly were edematous and hemorrhagic changes inside and outside alveoli in lung, with sever destructive and necrotic with hemolytic changes in livers .Reported results' concluded that most cystic lesions' specimens were presented in lung , liver which were infected with bacteria Klebsiella pneumonia.